2017
DOI: 10.1136/sextrans-2016-053046
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of prevalent HPV and STI co-infections and associated factors among HIV-negative young Western Cape, South African women: the EVRI trial

Abstract: NCT01489527; Post-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
(43 reference statements)
5
26
1
2
Order By: Relevance
“…A high burden of concurrent STIs was observed in this study, similar to a recently reported study among Western Cape young women [ 34 ]. In addition to HPV, other STIs increase the risk of HIV acquisition and transmission [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…A high burden of concurrent STIs was observed in this study, similar to a recently reported study among Western Cape young women [ 34 ]. In addition to HPV, other STIs increase the risk of HIV acquisition and transmission [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol ( 70 ) and tobacco use ( 71 - 73 ) also have a correlation with increased HPV infection independent of the number of sexual partners, so avoidance of these substances is advisable. A study of South African women showed high rates of co-infection with sexually-transmitted infections and HPV, most commonly herpes simplex type 2 and chlamydia trachomatis ( 74 ). Likewise, higher number of sexual partners has been repeatedly demonstrated as a risk factor for genital HPV infection ( 29 , 66 , 75 - 77 ).…”
Section: Current Therapies Against Hpvmentioning
confidence: 99%
“…A staggering 44% of women were infected with Chlamydia, 16% of whom had at least one additional STI. The Chlamydia infection rate among these women is substantially higher than reported among young sexually active women from other parts of SA, including rural KwaZulu-Natal (25%) (Kleppa et al 2015) and a different area in Cape Town (15%) (Menezes et al 2017). STI management remains problematic in developing countries where laboratory-based testing is frequently unavailable and where quality of STI care may be lacking (availability of medications, adherence to STI guidelines, condom provision and partner notification counselling [Kohler et al 2017]).…”
Section: Discussionmentioning
confidence: 98%